Vytápění s pomocí kondenzační techniky - Jadrníčková, Kateřina (Vysoké učení technické v Brně. Fakulta stavební, 2018)
Předmětem této bakalářské práce je návrh vytápění a přípravy teplé vody administrativního objektu v areálu Svit ve Zlíně. Objekt má tři nadzemní podlaží. Jako zdroj tepla jsou zde navrženy plynové kondenzační kotle. V teoretické části A je řešena problematika plynových kondenzačních kotlů. Výpočtová část B se zabývá návrhem otopné soustavy, přípravou teplé vody a pojistných, expanzních a dalších zařízení nutných k návrhu ústředního vytápění. Poslední část C tvoří technická zpráva a výkresová dokumentace vytápění objektu.

The subject of this bachelor thesis is the design of heating and hot water preparation of an administrative building in the complex Svit in Zlín. The building has three above-ground floors. As a source of heat are designed gas condensing boilers here. In the theoretical part A is solved the problem of gas condensing boilers. The computational part B deals with the design of the heating system, the preparation of hot water and the safety, expansion and other equipment necessary for the design of central heating. The last part C consists of the technical report and the drawing documentation of the heating of the building.
Heating using condensing technology
Keywords: Vytápění; administrativní budova; příprava teplé vody; plynová kotelna; plynové kondenzační kotle; desková otopná tělesa; tepelný výkon; dimenzování otopné soustavy.; Heating; administrative building; hot water preparation; gas boiler room; gas condensing boilers; panel radiators; heating power; dimensioning of the heating system.